Pain control in trauma patients in emergency departments: current status and influencing factors - Wei, Zinian (Frontiers in Public Health, 2025)
ObjectiveTo investigate the current status of pain control in trauma patients in the emergency department, as well as nurses’ attitudes, behaviors, and influencing factors regarding pain management, with the aim of improving the quality of emergency care.MethodsA single-center cross-sectional study was conducted. Using convenience sampling, 245 trauma patients admitted to the emergency department of Suzhou Research Center of Medical School, Suzhou Hospital, Affiliated Hospital of Medical School, between January and December 2024 were enrolled, along with 79 emergency nurses. Patients were assessed using the Modified Early Warning Score (MEWS) and the Facial Rating Scale (FRS) for pain. Questionnaires were administered to both patients and nurses. Statistical analyses included descriptive statistics, t-tests, logistic regression, and multiple linear regression.ResultsThe majority of patients were male (68.16%) and aged 18–60 years (80.82%). The most common injuries were limb (41.63%) and chest-abdominal (31.43%), with traffic accidents as the leading cause (40.00%). Analgesic administration rates increased with MEWS scores (0% in MEWS 0–2, 44.0% in 5–6, and 67.9% in ≥9). However, patient satisfaction did not increase correspondingly (29.21% in MEWS 3–4, 34.00% in 5–6). Nurses expressed strong concern that analgesia may mask clinical conditions (mean score 4.29 ± 0.56). Logistic regression showed that main injury site (OR = 0.69, p = 0.014), injury type (OR = 2.18, p = 0.001), analgesia request (OR = 1.68, p = 0.004), and injury manifestation (OR = 1.62, p = 0.003) were independent predictors of satisfaction. Multiple linear regression confirmed analgesia request (β = 0.32, p < 0.001) and obvious injury manifestation (β = 0.25, p = 0.002) as positive predictors, while limb injuries predicted lower satisfaction (β = −0.19, p = 0.008).ConclusionPain control in emergency trauma patients is influenced by injury severity, nurses’ attitudes, and patient-related factors. Comprehensive pain assessment, nurse training, and consideration of patient requests and injury characteristics are essential to improving emergency pain management.